UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MENERAPKAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DI KELAS V SD NEGERI 068003 SIMALINGKAR: Penelitian Tindakan Kelas - Br Sembiring, Agnes Salsalina; Gaol, Rumiris Lumban; Sitorus, Irmatansy Alodya; Tarigan, Chindi Clodiya Br; Karo, Jumpa Kita Agata Purba; Josua Sembiring, Josua Sembiring (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This research was motivated by the low mathematics learning outcomes of fifth-grade students at SD Negeri 068003 Simalingkar, which were attributed to the unengaging conventional teaching methods. The objective of this study was to improve mathematics learning outcomes through the implementation of the Teams Games Tournament (TGT) learning model. The research employed a Classroom Action Research (CAR) method based on the Kurt Lewin model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The results showed that in the first cycle, the average student score increased from 49.74 to 55.53, but this improvement was not statistically significant (p = 0.157). After improvements in the second cycle, the average score increased significantly from 57.86 to 80.48 (p = 0.000). These findings indicate that the TGT model effectively enhances mathematics learning outcomes. Therefore, the TGT model can be recommended as an alternative teaching strategy in elementary schools, particularly in mathematics subjects.